Molluscs of the Holm Dal Formation (late Middle Cambrian), central North Greenland - Peel, John S. (Meddelelser om Grønland. Geoscience, 1988)
A small, but diverse fauna of molluscs is described from the lower beds of the Holm Dal Formation (late Middle Cambrian) of central North Greenland. Species of Helcionellacea and Hypseloconellacea dominate, although only individuals of the former superfamily are numerically common, as are examples of a single stenothecoid species. Paragastropoda and Hyolitha are rare faunal elements. A single newgenus (Perssuakiella) and 5 new species are described: P. troelseni, Latouchella holmdalense, L. pearylandica, Stenothecoides groenlandica and Costipelagiella kochi.